Cyclic tests on a hybrid coupled wall utilizing a rocking mechanism. - Hitaka, Toko
A new type of hybrid coupled wall system, consisting of rolled steel coupling beams, reinforced concrete (RC) wall piers, and concrete-filled tube (CFT) short columns, is introduced. In this new system, the bases of the wall piers are connected to the base beams only through CFT short columns, unlike conventional coupled walls. Yield occurs in the coupling beams and the short columns; hence, in the RC wall piers, only minimum cracking appears. A total of four subassembly specimens, designed to fail in various collapse mechanisms, were cyclically loaded under constant axial force. A benchmark specimen showed ductile behavior with large energy dissipation until fracture occurred in the coupling beam. In the specimen designed to fail in shear in its CFT, substantial axial shortening was observed, but the overall behavior was ductile. Behavior of specimens with small amounts of section steel in the wall panel fringe, or with thin wall panels, also showed ductile behavior, but the strength and energy dissipation were significantly smaller than other two specimens. An analytical model was proposed for a frame analysis program using fiber elements to simulate elastic?plastic behavior of the system. Design methods to prevent shear failure of CFT and RC panels are suggested using the analytical and test results.
Keywords: Building; CFT; Composite; Coupling beam; Cyclic test; Hysteresis